Multi-vortex states in magnetic nanoparticles - Gan, W. L. (2014)
We demonstrate a fabrication technique to create cylindrical NiFe magnetic nanoparticles (MNPs) with controlled dimensions and composition. MNPs thicker than 200 nm can form a double vortex configuration, which consists of a pair of vortices with opposite chirality. When MNPs thicker than 300 nm are relaxed after saturation, it forms a frustrated triple vortex state which produces a higher net magnetization as verified by light transmissivity measurements. Therefore, a greater magnetic torque can be actuated on a MNP in the triple vortex state.